Transdiagnostic ecological momentary intervention for improving self-esteem in youth exposed to childhood adversity: the SELFIE randomized clinical trial: research - Reininghaus, Ulrich; Daemen, Maud; Postma, Mary Rose; Schick, Anita; Hoes-van der Meulen, Iris; Volbragt, Nele; Nieman, Dorien; Delespaul, Philippe; de Haan, Lieuwe; van der Pluijm, Marieke; Breedvelt, Josefien Johanna Froukje; van der Gaag, Mark; et al. (JAMA psychiatry, 2024)
Targeting low self-esteem in youth exposed to childhood adversity is a promising strategy for preventing adult mental disorders. Ecological momentary interventions (EMIs) allow for the delivery of youth-friendly, adaptive interventions for improving self-esteem, but robust trial-based evidence is pending.To examine the efficacy of SELFIE, a novel transdiagnostic, blended EMI for improving self-esteem plus care as usual (CAU) compared with CAU only.This was a 2-arm, parallel-group, assessor-blinded, randomized clinical trial conducted from December 2018 to December 2022. The study took place at Dutch secondary mental health services and within the general population and included youth (aged 12-26 years) with low self-esteem (Rosenberg Self-Esteem Scale [RSES] <26) exposed to childhood adversity.A novel blended EMI (3 face-to-face sessions, email contacts, app-based, adaptive EMI) plus CAU or CAU only.The primary outcome was RSES self-esteem at postintervention and 6-month follow-up. Secondary outcomes included positive and negative self-esteem, schematic self-beliefs, momentary self-esteem and affect, general psychopathology, quality of life, observer-rated symptoms, and functioning.A total of 174 participants (mean [SD] age, 20.7 [3.1] years; 154 female [89%]) were included in the intention-to-treat sample, who were primarily exposed to childhood emotional abuse or neglect, verbal or indirect bullying, and/or parental conflict. At postintervention, 153 participants (87.9%) and, at follow-up, 140 participants (80.5%), provided primary outcome data. RSES self-esteem was, on average, higher in the experimental condition (blended EMI + CAU) than in the control condition (CAU) across both postintervention and follow-up as a primary outcome (B = 2.32; 95% CI, 1.14-3.50; P < .001; Cohen d-type effect size [hereafter, Cohen d] = 0.54). Small to moderate effect sizes were observed suggestive of beneficial effects on positive (B = 3.85; 95% CI, 1.83-5.88; P < .001; Cohen d = 0.53) and negative (B = −3.78; 95% CI, −6.59 to −0.98; P = .008; Cohen d = −0.38) self-esteem, positive (B = 1.58; 95% CI, 0.41-2.75; P = .008; Cohen d = 0.38) and negative (B = −1.71; 95% CI, −2.93 to −0.48; P = .006; Cohen d = −0.39) schematic self-beliefs, momentary self-esteem (B = 0.29; 95% CI, 0.01-0.57; P = .04; Cohen d = 0.24), momentary positive affect (B = 0.23; 95% CI, 0.01-0.45; P = .04; Cohen d = 0.20), momentary negative affect (B = −0.33; 95% CI, −0.59 to −0.03, P = .01, Cohen d = −0.27), general psychopathology (B = −17.62; 95% CI, −33.03 to −2.21; P = .03; Cohen d = −0.34), and quality of life (B = 1.16; 95% CI, 0.18-2.13; P = .02; Cohen d = 0.33) across postintervention and follow-up. No beneficial effects on symptoms and functioning were observed.A transdiagnostic, blended EMI demonstrated efficacy on the primary outcome of self-esteem and signaled beneficial effects on several secondary outcomes. Further work should focus on implementing this novel EMI in routine public mental health provision.Dutch Trial Register Identifier:NL7129(NTR7475)